The cost and cost drivers of delivering COVID-19 vaccines in low- and middle-income countries: a bottom-up costing study of rollouts in seven countries - Flavia Moi; Van Minh Nguyen; Rachel Archer; Tozé Namalela; Christina Banks; Tarek Hossain; Afroja Yesmin; Cathbert Tumusiime; Charlotte Muheki; Kelsey Vaughan; Elise Smith; Rafael Deo Estanislao; et al. (PLoS ONE, 2026)
Introduction While COVID-19 vaccines were crucial in containing the pandemic, there is limited evidence on the cost of delivering them in low- and middle-income countries. We estimated the cost of delivering COVID-19 vaccines in Bangladesh, Côte d’Ivoire, the Democratic Republic of the Congo, Mozambique, the Philippines, Uganda, and Vietnam. Methods We retrospectively estimated the financial and economic cost of COVID-19 vaccine delivery from a payer perspective, using a bottom-up approach. Cost data were collected from 290 sites, while qualitative interviews were conducted with 192 key informants. We estimated volume-weighted average costs per dose in 2022 USD, for introduction phases, delivery modalities, and strategies. Results The financial cost per dose ranged from $0·29-$2·18 across countries, driven by per diem and supplies. The economic cost per dose ranged from $1·14-$9·50, driven by the cost of labor. Newly hired health workers were a cost driver only in the Philippines. The economic delivery cost per dose was inversely correlated with daily vaccine volume delivered at vaccination sites. Similarly, delivering through campaigns came at a lower unit cost than continuous delivery, and when programs scaled up, the cost per dose decreased dramatically. Political prioritization, health workers’ commitment, and volunteers were highlighted as success factors, while resource constraints at implementation level and health workers shortages were flagged as key challenges. Conclusion Our findings demonstrate how under-resourced health systems managed to deliver massive amounts of vaccines with relatively few resources. However, they also expose significant gaps and inefficiencies, and underscores the need to invest in resilient health systems to improve future pandemic responses.